1970
DOI: 10.3329/imcj.v2i2.2936
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrom in Three Urban Communities of Dhaka City

Abstract: Bangladeshis are prone to develop type 2 diabetes mellitus (T2DM), hypertension (sHTN and dHTN) and atherosclerotic heart diseases, observed more predominantly in the urban population. Though metabolic syndrome (MetS) is a related disorder, there are few studies in this regard. The prevalence of obesity, T2DM and MetS in three urban communities of Bangladesh were addressed in this study. Nine hundred non-slum urban households in three Dhaka City Wards were randomly selected. One member (age ≥ 25y) from each ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…7-9 A study carried out among adult population in Bangladesh has found higher prevalence of metabolic syndrome in females using International Diabetes Foundation (IDF) criteria. 21 We did not find age, family history of diabetes to be associated with metabolic syndrome in agreement with Cook et al 7 In the present study the waist-hip ratio in obese children in all age group was more than 0.9 indicating abdominal adiposity. Waist -hip ratio is an excellent predictor of abnormalities of lipids and glucose metabolism in the adult population and similar correlation have been made for paediatric obesity 22 .…”
Section: Discussionsupporting
confidence: 82%
“…7-9 A study carried out among adult population in Bangladesh has found higher prevalence of metabolic syndrome in females using International Diabetes Foundation (IDF) criteria. 21 We did not find age, family history of diabetes to be associated with metabolic syndrome in agreement with Cook et al 7 In the present study the waist-hip ratio in obese children in all age group was more than 0.9 indicating abdominal adiposity. Waist -hip ratio is an excellent predictor of abnormalities of lipids and glucose metabolism in the adult population and similar correlation have been made for paediatric obesity 22 .…”
Section: Discussionsupporting
confidence: 82%
“… 39 42 47 Furthermore, 11 studies were conducted in rural areas, 11 26 27 30–32 35 38 40 45 46 4 in urban areas, 12 24 33 44 7 studies in both settings 25 29 39 41–43 47 and 1 study in a suburban area. 34 The proportion of male participants ranged from 9% to 67% and the percentage of obese or overweight participants ranged from 5.7% to 47.2%. The average age of participants ranged from 31.3 to 51.48 years.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time a significant portion of the population have conditions such as IFG or IGT, and therefore are at risk of developing T2DM [14,30,35]. For example, in our reviewed studies, the pooled prevalence for IFG and IGT were found 7.0% (95%CI: 3.2%–10.8%, I 2  = 99%) and 8.2% (95%CI: 3.9%–12.4%, I 2  = 99%), respectively [10,16,22,25,30,31,33,35,36]. …”
Section: Discussionmentioning
confidence: 99%